Sinclair broadcasting as mini-media empire: media regulation, disinfomercials, and the rise of Trumpism. (October 2020) - Tryon, Chuck
This article argues that Sinclair Broadcast Group (SBG) should be read as a mini-network, one that has used lenient regulations to build a vast empire of affiliate stations, which allows them to maintain substantial control over local news in markets across the United States. In turn, drawing from close readings of SBG news segments, this essay argues that SBG has used this platform to promote a conservative political stance, one that deploys the discourses of mediated populism. Finally, although research on political media has tended to focus on cable news, it is important to analyze the ways in which SBG and other affiliate owners can exert significant control over local news, one of the most trusted sources of news for many people in the United States.